SIKAP TERHADAP MUSIK DANGDUT - Clara Moningka; Dina Argitha; Gretha Gretha (Psibernetika, 2014)
Dangdut has become one of Indonesia iconic music. This music is the result of a blend of music from India with Melayu music. The distinctive feature lies in the melody of dangdut who came from music instruments; tabla (a type of percussion instrument that produces sound like"ndut"). The meaning of dangdut songs, are usually easy to understand, so it's not hard to be accepted every people of any social economy class. Despite of its popularity dangdut music also gets a lot of controversy, because of the body movements or dance which are considered erotic. Based on the facts about dangdut, researchers are interested in measuring the attitude towards the dangdut music. Percentage of the data obtained shows that public attitudes towards the dangdut music in Jakarta is on the lower level (not interested or negative) (52% or26 of 50 respondents).Keywords: Dangdut music, attitude